Premature destruction of two-span RC beams exposed to high temperature caused by a redistribution of shear forces - Kowalski, Robert; Głowacki, Michał; Abramowicz, Marian (Journal of Civil Engineering and Management, 2017)
When multi-span RC elements are exposed to fire one usually observes a yielding of span cross-sections while a safety reserve of support cross-sections is still significant. Due to this phenomenon a redistribution of bending moments occurs and the values of sagging moment in span cross-sections decrease while the values of hogging moment in support cross-sections increase. This paper shows the results of tests conducted on two-span RC beams in a situation when only one span has been exposed to high temperature from the bottom. The beams were 12×16 cm in their cross-section. The length of the span was 165 cm. The load has been applied by two forces put on each span. The beams were made of C25/30 concrete with siliceous aggregate. As a result of significant stiffness decrease of the heated span, redistribution of shear forces and bending moment occurs. Due to this redistribution the tested beams were prematurely damaged due to exhaust of the shear load bearing capacity in the middle part of the beam span where there was no transverse reinforcement. First published online: 27 Jun 2016